Increased HMGB1 expression correlates with higher expression of c-IAP2 and pERK in colorectal cancer. Issue 3 (January 2019) - Zhang, Wenjia; An, Fangmei; Xia, Min; Zhan, Qiang; Tian, Wenying; Jiao, Yang
Abstract : Abstract: The aim of this study was to investigate the relationship between high-mobility group box 1 (HMGB1) and colorectal cancer (CRC). In this prospective study, patients with CRC undergoing primary surgery and healthy subjects (control group) were enrolled from July 2013 to December 2014. The serum HMGB1 concentration and HMGB1 mRNA expression were determined using enzyme-linked immunosorbent assay reverse transcription-polymerase chain reaction, respectively. Immunohistochemical analysis was performed to determine HMGB1, pERK, and c-inhibitor of apoptosis protein 2 (c-IAP2) protein expression levels in the cancer tissues. A total 144 patients with CRC and 50 healthy subjects underwent serum HMGB1 testing. Resected specimens of 50 patients were used for HMGB1 mRNA and protein expression analyses. Mean serum HMGB1 level in the patients with CRC was higher than that of the control group (8.42 μg/L vs 1.79 μg/L, P  < .05). Mean serum HMGB1 level in the patients with CRC with distant metastasis was significantly higher than that of the controls (13.32 μg/L vs 7.37 μg/L, P  < .05). The HMGB1 mRNA and protein expression levels in the CRC tissues were significantly higher than those in the adjacent normal mucosa. HMGB1 protein expression positively correlated with the lymph node metastasis. There were positive correlations between HMGB1 and c-IAP2 ( r  = 0.457, P  < .05), HMGB1 and pERK ( r  = 0.461, P  < .05), as well as pERK and c-IAP2 ( r  = 0.399, P  < .05). HMGB1 expression in CRC correlates with distant and lymph node metastasis. It may inhibit apoptosis by inducing activation of pERK and c-IAP2.